PENGEMBANGAN MODUL AJAR BERBASIS MODEL SCRUM SEBAGAI INOVASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SKI - Muhammad Maulana Husin; Jasiah Jasiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to develop a Scrum-based teaching module as an innovation to improve students' learning motivation in the subject of Islamic Cultural History (SKI). The research method used is Research and Development with the ADDIE model approach, which includes needs analysis, design, development, implementation, and evaluation. The results of the study indicate that the implementation of Scrum-based teaching modules can significantly increase student involvement and motivation in the learning process. The collaborative and interactive approach in the teaching module makes students more connected to the material being studied, thus having a positive impact on their understanding and learning outcomes. Thus, the development of this teaching module is expected to be an effective solution to overcome existing learning challenges and stimulate students' interest in learning SKI.